2020
DOI: 10.1186/s12886-020-01668-7
|View full text |Cite
|
Sign up to set email alerts
|

Short-term changes in the anterior segment and retina after small incision lenticule extraction

Abstract: Background To analyse short-term changes in the anterior segment and retina after small incision lenticule extraction (SMILE). Methods Patients with myopia scheduled for SMILE were recruited from Ruijin Hospital, Shanghai, China. Basic patient information such as age, sex, and refractive errors was recorded. Ocular measurements were taken before surgery, and 1 day and 1 week after surgery; they included axial length (AL), central corneal thickness (CCT), anterior chamber depth (ACD), lens thickness (LT), whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…The trends in the postsurgical retinal indices in our study differed from those reported before (10,19). Shen et al divided the macular area into three zones: the foveal avascular zone (FAZ), the parafoveal area, and the perifoveal area.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The trends in the postsurgical retinal indices in our study differed from those reported before (10,19). Shen et al divided the macular area into three zones: the foveal avascular zone (FAZ), the parafoveal area, and the perifoveal area.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the exact way of dividing and measuring was not explained. The authors concluded that the vascular density returned to baseline values 1 week after SMILE in all areas except the FAZ zone (10). Using a similar division method, Gong et al reported that 2 weeks after SMILE, the vascular density of the macular area returned to baseline levels, whereas superficial retinal vessel density (VD) in the parafoveal and perifoveal areas remained unchanged (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, after 1 month, the area near the center of the macula returned to the preoperative level. Similarly, Yanwei Chen et al [31] found that the vascular density in and around the optic disc decreased 1 day after SEILE but returned to normal 1 week after the surgery. Another study [32] indicated that after FS-LASIK, the vascular density initially decreased and then increased, ultimately returning to the preoperative level after 1 month.…”
Section: Discussionmentioning
confidence: 76%
“…High intraocular pressure changes the ocular blood circulation and perfusion, which can lead to the interruption of the axoplasmic flow of retinal nerve fibers, axonal disintegration, apoptosis of retinal ganglion cells, and or even defect of RNFL. Abnormal blood flow in the eye leads to the reduced blood supply to the eye, leading to chronic ischemia and hypoxia, which in turn can cause RNFL thinning or even defect [40] . In conclusion, these data and findings contribute to the assessment of factors associated with RNFLD, and to predict and evaluate diseases related to RNFLD.…”
Section: Subjects and Methods Ethical Approvalmentioning
confidence: 99%